Problematika Penerapan Accrual Accounting Pada Lembaga Keuangan Syariah - Elyanti Rosmanidar; Youdhi Prayogo (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2022)
Today, there is much debate about the basic assumptions that should be used in the financial statements of Islamic entities, namely the accrual basis and cash basis. This study will reveal that the accrual basis which is widely applied in the preparation of financial statements turns out to have many gaps to manipulate data, so that it will cause earnings management to arise. The unpopular cash basis applied in the preparation of financial reports is more able to reveal real conditions, income and expenses. This study also discusses the reasons for using the accrual basis in the framework for preparing and presenting Islamic financial statements based on PSAK 101 whereby Islamic entities must prepare financial statements on an accrual basis. This research will also show the many problems that arise in the application of accrual accounting in Islamic financial institutions today.